Cancer of corpus uteri in women aged 70 and older. Evaluation of early post-radiation reactions - Helis, Karolina; Urbańczyk, Hubert (Menopause Review/Przegląd Menopauzalny, 2011)
Objectives : The objective of the study was to evaluate the tolerance of radical radiotherapy in patients with cancer of the corpus uteri, aged 70 years and older. Materials and methods : The analysis is based on 94 patients with cancer of the corpus uteri. There were 94 women aged 70-85 years (median 74 years) treated using radical radiotherapy in the Department of Radiotherapy, Maria Sklodowska-Curie Memorial Cancer Centre and Institute of Oncology, Gliwice Branch in Poland during 2008 to October 2010. Acute treatment toxicity was assessed using the EORTC/RTOG scale. The skin reaction, the digestive system reaction and urinary tract reaction were analysed. Results : The most frequent early acute post-radiation reaction was bowel reaction (74.5%) in comparison with skin (24.5%) and urinary bladder (15.96%) reactions. A severe bowel reaction, adynamic ileus, was observed in 4 patients. There were no severe reactions of the urinary bladder. Benign reactions of the bladder were observed in 15 patients (15.96%). Severe skin reactions in 1 (1.06%) patient and benign reaction in 22 (23.4%) were observed. In the majority of patients there were no skin reaction (75.5%). Conclusion : Radical radiotherapy in senile patients with cancer of the corpus uteri is combined with higher frequency of early acute toxicity, but still remains a safe and well-tolerated method of treatment.